Antibody responses in Burkinabe children against P. falciparum proteins associated with reduced risk of clinical malaria - Yuguchi, Takaaki; Dankyi, Benedicta O.; Rojrung, Rattanaporn; Nagaoka, Hikaru; Kanoi, Bernard N.; Tiono, Alfred B.; Nebie, Issa; Ouedraogo, Alphonse; Miura, Kazutoyo; Sattabongkot, Jetsumon; Sirima, Sodiomon B.; Tsuboi, Takafumi; et al. (Frontiers in Immunology, 2025)
Individuals residing in malaria-endemic regions with high disease transmission can develop semi-immunity within five years of age. Although understanding the target of the IgGs in this age group helps discover novel blood-stage vaccine candidates and serological markers, it has not been well elucidated due to limited accessibility to plasmodial antigens and samples. This study presents the first comprehensive analysis of antibody levels in plasma obtained from Burkinabe children (n=80, aged 0 to 5 years) to 1307 Plasmodium falciparum proteins expressed by the eukaryotic wheat germ cell-free system. Antibody levels were measured by AlphaScreen. We found that 98% of antigens were immunoreactive. The number of reactive antigens by the individual was correlated with increasing age. The most significant increases in seroprevalence occur during the first 2 years of life. By correlating antibody levels and the number of clinical malaria during a 1-year follow-up period, we identified 173 potential protein targets which might be associated with clinical immunity. These results provide valuable insights into how children acquired semi-immunity to malaria in their early lives.